Analysis of software defined security model and architecture - Chunmei GUO; Jun MA; Hao GUO; Xueyao BI; Ruhui ZHANG; Shaomin ZHU; Congyi YANG (Dianxin kexue)
Currently,most enterprises have deployed information security defense system based on policy access control.With cloud computing environment deployment and network attacking technology development,security has been regarded as one of the greatest problems in the cloud computing environment.The advanced persistent attacks including of bypassing the traditional firewall easily,breaking through the black and white list and feature matching of the security defense mechanism have included to the traditional security system new challenges.The problem in the traditional tightly coupled security defense system of combining the virtual with the true for construction of network environments was described,and a software defined security model and framework was provided.The decoupling scheme of access patterns and deployment position in combining the virtual with the true for construction of network environments was realized,which provided a beneficial exploration in the field of the adaptive active safety for enterprise cloud computing environment.